Mango powder - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Dried mango powder, which is easily made into a drink, a paste or a jam, and which keeps well is the result of research by GRAT (Group de recherche et d'applications techniques), a Malian NGO. The mangoes are dried and then ground into powder...